The role of landscape structure in species richness distribution of birds, amphibians, reptiles and lepidopterans in Mediterranean landscapes - Atauri, J. A.; Lucio, J. V. De (Landscape ecology, 2001)
The parameters referring to landscape structure are essential in any evaluation for conservation because of the relationship that exists between the landscape structure and the ecological processes. This paper presents a study of the relationships between landscape structure and species diversity distribution (estimated in terms of richness of birds, amphibians, reptiles and butterﬂies) in the region of Madrid, Spain. The results show that the response of species richness to landscape heterogeneity varies depending on the group of species considered. For birds and lepidopterans, the most important factor affecting the distribution of richness of species is landscape heterogeneity, while other factors, such as the speciﬁc composition of land use, play a secondary role at this scale. On the other hand, richness of amphibians and reptiles is more closely related to the abundance of certain land-use types. The study highlights the importance of heterogeneity in Mediterranean landscapes as a criterion for landscape planning and for deﬁnition of management directives in order to maintain biodiversity
Keywords: diversity distribution; landscape ecology; landscape heterogeneity; species richness distribution

The role of landscape structure in species richness distribution of birds, amphibians, reptiles and lepidopterans in Mediterranean landscapes - Atauri, J A; Lucio, J V De (Landscape ecology, 2001)
The parameters referring to landscape structure are essential in any evaluation for conservation because of the relationship that exists between the landscape structure and the ecological processes. This paper presents a study of the relationships between landscape structure and species diversity distribution (estimated in terms of richness of birds, amphibians, reptiles and butterﬂies) in the region of Madrid, Spain. The results show that the response of species richness to landscape heterogeneity varies depending on the group of species considered. For birds and lepidopterans, the most important factor affecting the distribution of richness of species is landscape heterogeneity, while other factors, such as the speciﬁc composition of land use, play a secondary role at this scale. On the other hand, richness of amphibians and reptiles is more closely related to the abundance of certain land-use types. The study highlights the importance of heterogeneity in Mediterranean landscapes as a criterion for landscape planning and for deﬁnition of management directives in order to maintain biodiversity
Keywords: diversity distribution; landscape ecology; landscape heterogeneity; species richness distribution